Complete Genome Sequence and Annotation of the Paracoccus pantotrophus Type Strain DSM 2944 - Bockwoldt, Julia A. (Microbiol Resour Announc, 2020)
Paracoccus spp. are metabolically versatile alphaproteobacteria able to perform heterotrophic and chemoautotrophic growth. This study describes the whole-genome sequence of the Paracoccus pantotrophus type strain DSM 2944 (ATCC 35512, LMD 82.5, GB17). The genome sequence revealed the presence of a complete phaZ phaC phaP phaR gene cluster related to polyhydroxyalkanoate metabolism.